A unique case of AH-dominant type nodular pulmonary amyloidosis presenting as a spontaneous pneumothorax: a case report and review of the literature - Valeria Skopelidou; Valeria Skopelidou; Pavel Hurník; Pavel Hurník; Pavel Hurník; Lubomír Tulinský; Lubomír Tulinský; Vladimir Židlík; Vladimir Židlík; Vladimir Židlík; Jiří Lenz; Patricie Delongová; et al. (Frontiers Media S.A., 2023)
Amyloidosis is a rare metabolic disorder primarily brought on by misfolding of an autologous protein, which causes its local or systemic deposition in an aberrant fibrillar form. It is quite rare for pulmonary tissue to be impacted by amyloidosis; of the three forms it can take when involving pulmonary tissue, nodular pulmonary amyloidosis is the most uncommon. Nodular pulmonary amyloidosis rarely induces clinical symptoms, and most often, it is discovered accidentally during an autopsy or via imaging techniques. Only one case of nodular pulmonary amyloidosis, which manifested as a spontaneous pneumothorax, was found in the literature. In terms of more precise subtyping, nodular amyloidosis is typically AL or mixed AL/AH type. No publications on AH-dominant type of nodular amyloidosis were found in the literature. We present a case of an 81 years-old male with nodular pulmonary AH-dominant type amyloidosis who presented with spontaneous pneumothorax. For a deeper understanding of the subject, this study also provides a review of the literature on cases with nodular pulmonary amyloidosis in relation to precise amyloid fibril subtyping. Since it is often a difficult process, accurate amyloid type identification is rarely accomplished. However, this information is very helpful for identifying the underlying disease process (if any) and outlining the subsequent diagnostic and treatment steps. Even so, it is crucial to be aware of this unit and make sure it is taken into consideration when making a differential diagnosis of pulmonary lesions.